Numerical simulation simulation of MHD mixed convection in a nanofluid filled non-darcy porous enclosure - Begum, A. Shamadhani; Nithyadevi, N.; Öztop, Hakan Fehmi; Al-Salem, Khaled (Pergamon-Elsevier Science Ltd, 2017)
This paper examines numerically the thermal and flow field characteristics of the mixed convection flow in a rectangular lid-driven porous enclosure filled with Cu-water nanofluid subjected to the influence of an inclined uniform magnetic field. The enclosure has sinusoidal heating vertical walls, thermally insulated horizontal walls and a heated moving lid at the centre of the enclosure move at a uniform velocity. The non-linear governing equations and boundary conditions are discretized using finite volume approach with power law scheme and solved numerically by SIMPLE algorithm for the pressure-velocity coupling together with under relaxation technique. Numerical study has been carried out for different values of Richardson number (0.01 <= Ri <= 100), Darcy number (10(-3) <= Da <= 10(-3)), Hartmann number (0 <= Ha <= 100), orientation of magnetic field (0 degrees <= gamma <= 90 degrees), solid volume fraction (0.0 <= phi <= 0.1) and described in the form of streamlines, isotherms, average Nusselt number and velocity graphs. Based on the obtained results, it is found that Hartmann number and the orientation of the magnetic field have adverse impact on convection, hence dominated conduction mode occurs. Moreover, it leads to the reduction of overall heat transfer rate. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Lid-driven; Porous: nanofluid; Magnetic field; Sinusoidal heating